Steady-state performance investigation of closed-circuit hydrostatic system: A practical approach - Ajit Kumar Pandey; K. Dasgupta; N. Kumar (Kuwait Journal of Science)
This article studies the steady-state performance of a hydrostatic (HST) drive through modeling and experiment. The drive considered for the analysis has closed circuit configuration, where supply from the variable displacement pump drives a variable displacement hydro-motor. The torque-speed control of the hydrostatic drive is achieved by varying the pump or the motor displacement. The bond graph simulation technique is used to model the HST drive; where the losses of the pump and the hydro-motor are lumped through resistances. The characteristics of the losses are identified through test-data. The drive’s performance is examined for the torque-loss (%), slip and the overall efficiency at different load torque and motor speed. The predicted performance of the drive is obtained from the model and compared with the test-data. The studies made in the article identify the efficient zone of operation of the drive that will be useful for the application engineers to select such a drive in similar applications.